Strategic Management: Concept, Implementation, and Indicators of Success (Literature Review) - Candra Susanto, Primadi; Ali, Hapzi; Nyoman Sawitri, Ni; Widyastuti, Tri (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
The purpose of this study is to provide views and help prove the results of scientific articles by reviewing and providing perceptions from the author, The research method used is qualitative, by looking for library sources related to those used in this scientific article from reputable journals, google scholar, and others. The use of metric tables to help describe scientific articles that according to researchers are findings, the results of this study want to prove that there are references to concepts, implementations, and indicators that have not been proven directly by references to scientific articles or books, only from one article from (Ivan?i?, 2013) where the results of the research are The literature on strategy implementation and linking a number of critical points are important for reducing strategy implementation errors and improving organizational effectiveness, but all of that must be substantiated by follow-up research by other researchers. Researchers in the future, can sharpen and provide results in strategic management, especially with indicators specifically for both research and books.